2017
DOI: 10.1310/hpj5202-138
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct Analgesic Use for Acute Pain in the Emergency Department

Abstract: Purpose:Multimodal analgesia is common practice in the postoperative setting, but the utility of adjunctive analgesia in the emergency department (ED) is less understood. The primary objective of this study was to analyze ED prescriber ordering habits for adjunct nonopioid pain medication for opioid-naïve patients who require intravenous (IV) morphine or hydromorphone for acute pain. Secondary objectives were to assess initial and total opioid consumption in morphine equivalent units (MEU), pain scores, and ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…IV acetaminophen is infrequently used in the ED. 27 In the 2015 National Hospital Ambulatory Medical Care Survey it was only prescribed in 5 out of 21,000 visits. Hence, its role in the care of ED patients is relatively unknown.…”
Section: Discussionmentioning
confidence: 99%
“…IV acetaminophen is infrequently used in the ED. 27 In the 2015 National Hospital Ambulatory Medical Care Survey it was only prescribed in 5 out of 21,000 visits. Hence, its role in the care of ED patients is relatively unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it appears that 35% of patients in this study received hydromorphone as their initial analgesic. It has been shown that patients receive a larger number of morphine equivalent units when hydromorphone is administered compared to morphine . While it was found that larger milligram doses negatively influenced opioid response, the authors did not differentiate between patients receiving morphine versus hydromorphone.…”
mentioning
confidence: 96%
“…Second, reductions in pain scores are not the only measure of response to opioids. In a previous study, patients in both groups received similar total doses of opioids; however, patients who received adjunctive analgesics in addition to an opioid had a 48‐minute reduction in their emergency department (ED) treatment time, suggesting that the use of a multimodal regimen leads to faster disposition times and shorter ED length of stay.…”
mentioning
confidence: 99%
See 2 more Smart Citations